Globalization and inflation: The role of China - Denise Côté; Carlos De Resende (Bank of Canada, 2008)
In this paper, we develop a theoretical model which identifies four channelsimport prices, competition with domestic suppliers and workers, and commodity pricesthrough which priceand wage-setting conditions in country j may affect inflation in country i. We estimate a dynamic inflation equation derived from the theoretical model using a quarterly dataset of eighteen OECD countries over the 1984-2006 period. Although our methodology can be applied to any pair of countries, we focus on the effect of China on the inflation rate of other countries. Our results suggest that while China's negative effect on global inflation has been quantitatively modest, it has increased in absolute terms since the early 2000s. We also find evidence that, for most countries examined, competition with domestic suppliers has been the most important channel.
Keywords: E22; E32; E44; 330; International topics; Globalisierung; Internationale Wirtschaftsbeziehungen; Inflationsübertragung; Import; China; OECD-Staaten